(untitled) (Web of Teachers: Inderscience Research, 2024)
The author examines the key aspects of social intelligence, such as empathy, social perception, the ability to effectively communicate and resolve conflicts, as well as their role in the formation of a healthy educational climate. It is substantiated that social intelligence allows the heads of educational institutions to successfully adapt their activities to changing conditions, improve relationships within the team and increase the effectiveness of the educational process.